Optimalisasi AUM (Amal Usaha Muhammadiyah) Pada Pimpinan Cabang Muhammadiyah Kelayu - Nur Fitri Eka Asbarini; Baiq Dewi Kamariani; Abdul Chalel Rahman (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The branches manager or Pimpimpinan Cabang Kelayu was one of the Muhammadiyah PCMs in the East Lombok Region. The implementation of Muhammadiyah Branch activities experienced many obstacles so many activities were not carried out according to what was programmed. This is the background for holding optimization activities at PCM Kelayu so that it continues to provide benefits to the community, especially at PCM Kelayu. This research aims to find out how effective the Leadership and Community of Muhammadiyah Kelayu are in carrying out the activities that have been programmed. This activity was carried out using a community development model approach, namely an effort to prepare the community along with steps to strengthen community institutions so that they can realize progress, independence and prosperity in an atmosphere of sustainable social justice through the Real Work Lecture activities of the Muhammadiyah Selong Institute of Social and Health Technology. Based on the problems that have been identified, the solution offered in the KKN-PCM program is assistance in collecting data on Muhammadiyah residents and optimizing the renewal of several AUM facilities.